Chinese herbal medicine Shenqi compound for early intervention in patients at high cardiovascular risk of type 2 diabetes mellitus: the protocol of a multicenter, randomized, double-blind, placebo-controlled trial - Leng, Yulin; Zhang, Zehua; Yao, Nairong; Fu, Xiaoxu; Xie, Hongyan; Gao, Hong; Xie, Chunguang (Frontiers in Cardiovascular Medicine, 2024)
Introduction Reducing multiple cardiovascular risk factors is a key link and a challenging clinical problem to reduce the risk of cardiovascular complications and death in patients with diabetes. Currently, there is a lack of clinical studies on patients with diabetes combined with multiple risk factors. Traditional Chinese medicine is believed to have therapeutic effects that contribute to the comprehensive control of multiple cardiovascular factors. This study aims to provide evidence for the efficacy and safety of Shenqi compound (SQC) for early intervention in diabetic patients at high cardiovascular risk. Methods and analysis This study is a multicenter, randomized, double-blind, placebo-controlled trial. A total of 120 diabetic patients with high cardiovascular risk were enrolled in five research centers. After a 2-week run-in period, the intervention group received basic treatment and SQC granules, and the control group received basic treatment and placebo granules for a total of 24 weeks, with a 24-week follow-up. The endpoint outcomes are major adverse cardiovascular events and renal-related and peripheral vascular disease events. The primary efficacy outcome is carotid intima-media thickness, and the secondary efficacy outcomes are carotid shear stress, indicators of glucose and lipid metabolism, pancreatic islets function, hemorheology, traditional Chinese medicine syndrome score, and quality of life scale. Safety indicators and adverse events were used to assess the safety of SQC. Discussion This study comprehensively evaluated the efficacy and safety of SQC for early intervention in diabetic patients at high cardiovascular risk from the aspects of overall metabolic level, structure, and function of blood vessels, quality of life, and long-term follow-up of endpoint events, providing evidence-based evidence for the short-term efficacy and long-term benefits of early treatment to reduce the risk of diabetic cardiovascular complications. Trial Registration: This trial is registered in the Chinese Clinical Trial Registry on March 9, 2023, https://www.chictr.org.cn/showproj.html?proj=192803 (No. ChiCTR2300069219).